Xenophobia in South Africa - Zama Mthombeni (The Thinker)
Despite the human rights principles established in South Africa’s Constitution, there have been recurrent waves of xenophobia throughout the country’s history. Foreigners who live in South Africa have been perceived as the victims of xenophobia and South Africans as the perpetrators. This paper aims to problematise the usage of the ‘ubuntu’ ideology as a utopian African ethic to promote ‘universal’ African humanism. It seems that apartheid’s heritage, which produced the present-day South Africa in which these xenophobic events occur, is often overlooked when South Africans are characterised as xenophobic and in need of ubuntu salvation. The study makes the case that colonial and political issues, which continue to have an impact on high levels of poverty and unemployment, should be considered as ongoing contributors to xenophobia. Several anti-immigration organisations have emerged as discussion points in the country. This study will only concentrate on one of these: Operation Dudula. This paper critically examines the reasons why Operation Dudula is continuing to expand despite protests from civil society organisations. This paper demonstrates, via media stories, how the media primarily portrays the organisation as vigilante that vex ubuntu and African unification. The paper makes the claim that marginalised South Africans are ‘Native Foreigners’, as opposed to simply perpetrators, drawing on Neocosmos’ idea of native foreigners. Instead of being considered as a problem that needs ubuntu’s salvation, the paper argues that anti-immigrant organisations should be understood as a sign of unsolved colonial and political problems that need to be addressed.